THE EFFECT OF THICKNESS ON THE OPTICAL PROPERTIES OF INP QUANTUM DOTS GROWN ON GAAS SURFACES - Sharibaev M.; Saparniyazova G.; Bazarbayeva H. (Modern American Journals, 2026)
This work studies the influence of thickness on the optical properties of InP quantum dots. The spectral position of the maximum corresponding to the InP quantum dot is determined. With an increase in the thickness of the pseudomorphic InAs layer from 1.8 MS to 3 MS, along with a long-wave shift of the quantum dot FL band, its broadening occurred, which indicates the enlargement of quantum dots with simultaneous disorder in their size and shape.
Keywords: Quantum dot, energy shift, FL intensity, deformation.